2019
DOI: 10.35333/erd.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Attitude and Status of Turkish Dentistry Students

Abstract: Amaç: Diş Hekimliği Fakültesi'nde okuyan öğrencilerin kendi ağız ve diş sağlıklarının değerlendirilmesi bu çalışmanın amacıdır. Bunun sonucunda toplum ağız ve diş sağlığını etkileyecek olan geleceğin diş hekimlerine, kişisel sağlıklarını korumaları için etkili eğitim yöntemlerini geliştirecek fikirler üretilecektir. Materyal ve Metot: İnönü Üniversitesi Diş Hekimliği Fakültesi'nde eğitim gören 200 öğrenciye sosyodemografik, ağız diş sağlığı, beslenme düzeniyle ilişkili sorular içeren anket verilmiş, ardından h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…This result was not in agreement with the Kirchhoff et al who found that 71% of dental students used dental floss regularly (13). Özdal et al disagreed with our study , their results showed that 10% of the students stated that they use dental floss every day, 31% stated that they use2-3 times in a week .The percentage of those who do not use dental floss was found to be 36% (10).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This result was not in agreement with the Kirchhoff et al who found that 71% of dental students used dental floss regularly (13). Özdal et al disagreed with our study , their results showed that 10% of the students stated that they use dental floss every day, 31% stated that they use2-3 times in a week .The percentage of those who do not use dental floss was found to be 36% (10).…”
Section: Discussioncontrasting
confidence: 84%
“…Oral health affects general health, physical and social well-being (10). Preventive oral health knowledge, behavior and its practice are important ways of keeping our teeth and periodontal tissue health (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation